Beneficial effect of nanomaterials on the interfacial transition zone (ITZ) of non-dispersible underwater concrete. (26th July 2021) - Wang, Yaoyu; Zeng, Dahai; Ueda, Tamon; Fan, Yingfang; Li, Chuang; Li, Jiye
Highlights: The effects of three kinds of nanomaterials on ITZ of NUC were studied. The nano-SiO2 and nano-metakaolin could effectively modify the interfacial bond and the hardness strength. The nanomaterials could promote the formation of Ca(OH)2 crystals in the early stage of hydration. Considerable improvement in the microstructure of ITZ was achieved. Abstract: Non-dispersible underwater concrete (NUC) is a kind of widely used construction engineering material. It has added flocculant so that concrete can have the characteristics of inhibiting dispersion of cement and aggregate in an underwater environment. However, soluble salts (such as sodium chloride and calcium sulphoaluminate) in seawater can infiltrate the interfacial transition zone (ITZ) of concrete, and then the ionic binding ability of the crystal surface will be reduced, which will cause mass loss of bonding materials in an ITZ and lead to the reduction of mechanical properties of concrete. In order to solve the problem of weak mechanical properties of ITZ, in this study, the influences of three types nanomaterials (nano-SiO2, nano-metakaolin and nano-Al2 O3 ) were studied. These materials were added into concrete to improve the bond and hardness strength of ITZ, which could be characterized by a push-out test, nano indentation test, X-ray diffraction (XRD) and scanning electron microscope (SEM). The results indicated that the nano-SiO2 and nano-metakaolin could significantly increase the bond strength of ITZ at 3 d by 134.12% and 87.70%, respectively, and by 108.54% and 43.41%, respectively, at 28 d). When the addition of nano-SiO2 and nano-metakaolin was 3%, the modulus of ITZ was improved by 54.39% and 71.03%, respectively, compared with plain NUC. The XRD data displayed the fact that nanomaterials could promote the formation of calcium hydroxide (CH) at early stage of hydration, while they had a pozzolanic effect on the reduction of content of CH at later stage of hydration. The nano-SiO2 and nano-metakaolin could obviously improve the microscopic morphology. This study revealed that nano-SiO2 and nano-metakaolin could effectively enhance mechanical properties of NUC, thus enhancing anti-erosion and anti-scouring ability of NUC. It is believed that these findings could fulfill a better understanding of the role of nanomaterials in NUC.